(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2023)
This piece is a research essay investigating how Russians have reacted to the war in Ukraine and provides a contextual analysis of how Russian history and its socialization of its citizenry have impacted these reactions. To write this piece, I delved deep into primary and second sources about Russia, past and present, and analyzed social commentaries, poetry, and other media to supplement the factual research I collected. The majority of the Russian populace’s reactions express a conflict between their self-interest and their simultaneous resolute faith in Vladimir Putin. In my exploration of this topic, I found that by and large Russia’s tumultuous history directly shaped the current Russian temperament. As the war in Ukraine continues to press on to date, with causalities continuing to rise, Russian public opinion and the direction it veers to will have critical implications for all parties of the conflict. For additional context, listen to the author’s reflection on the piece below.